NEGOTIATION OF ORAL MEANING AND EQUALITY IN MULTI-MODAL TRANSLATION OF BILINGUAL DIGITAL STORYBOOKS - Kembaren, Farida Repelita Waty; Dewi, Utami; Fransiska , Widia; Faradilla, Faradilla (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2025)
This study examines how meaning and moral equality are negotiated in the multimodal translation of bilingual digital storybooks used in Indonesian primary education. Based on the Multimodal Discourse Translation and Analysis Study, this study adopts a qualitative multimodal case study design that focuses on the bilingual digital storybook Putri dans Hutan. The study involved a textual analysis of bilingual translation units, a multimodal analysis of visual and auditory elements, and classroom-based data collected through observation and interviews with teachers and students. These findings reveal that moral equity in bilingual digital storybooks is not only achieved through verbal translation but emerges through the interaction of translation strategies, multimodal resources, and translanguaging practices in the classroom. Dynamic equality is identified as the dominant translation strategy, especially in the morally charged segment, as it prioritizes emotional accessibility and moral clarity for young learners. When linguistic simplification reduces moral explicitness, visual and auditory elements play a compensatory role by reinforcing emotional cues and moral orientation. Classroom translation further mediates moral understanding, allowing students to negotiate and internalize moral meaning by utilizing Indonesian and English. This study contributes to translation studies by extending the concept of equality into multimodal and pedagogical contexts. It also offers practical implications for educators, translators, and digital media designers by highlighting the importance of multimodal coherence and classroom mediation in conveying moral values through bilingual digital storybooks.